Case Report: Twists and turns: a case of cervical mesonephric adenocarcinoma on contrast-enhanced ultrasound - Huang, Qiuyun; Luo, Yunhao; Xu, Jia; Ding, Kewen; Liu, Fangqin; Qiang, Lang (Frontiers in Oncology, 2026)
Cervical mesonephric adenocarcinoma is an extremely rare malignant tumor that originates from the mesonephric duct remnants on the lateral wall of the cervix and is a unique subtype of cervical epithelial tumors. Due to its rarity and non-specific clinical manifestations, early diagnosis is challenging. We report a case of 61-year-old female patient who presented with vaginal bleeding lasting over one month. Following conventional transvaginal ultrasound, contrast-enhanced ultrasound (CEUS), and magnetic resonance imaging (MRI) examination, MRI preliminary diagnosis suggested inflammatory lesions, while CEUS indicated malignant tumors. Finally, the patient underwent surgical treatment, and the pathological diagnosis was mesonephric adenocarcinoma of the cervix. Previous studies have shown that cervical mesonephric adenocarcinoma, often appears atypical on two-dimensional and color Doppler ultrasound. CEUS offers significant advantages in displaying the microvascular architecture of tumors and can provide more detailed and abundant perfusion information, thereby helping to improve the accuracy of diagnosis.